Role of microbial concrete in steel slag amended concrete structures - Kaur, Prabhdeep (My University, 2017)
Worldwide production of crude steel was a total of 1.63 billion metric ton in the year 2016. India being an emerging economy has a fast pace growth in industrial sector and is world’s third largest steel producer. The high production of steel not only includes economy-based concerns but also have environmental concerns associated with it. Bulk generation steel slag which is waste byproduct generated from steel industries involves disposal crises. The cement industry faces a number of challenges that include scarcity of raw materials and a perpetually increasing demand for concrete. The use of steel slag a source of fine aggregate replacement in concrete is a way for safe and economical utilization of waste byproducts. Along with the replacement, durability enhancement of the concrete harvesting Microbially induced calcium carbonate precipitation (MICCP), which is a biomineralization process is exploited in the current study. In the present study, calcifying bacteria PP9 isolated from steel slag was used to enhance the durability of cementitious material. Phylogenetic analysis of PP9 revealed 98.94% similarity to Staphylococcus pasteuri. The isolate PP9 was confirmed as non-pathogenic by coagulase test and mannitol salt agar. Urease assay quantitatively confirmed high urease production. Waste utilization was done by replacing fine aggregate in cement with steel slag (30% and 50%) along with MICCP carried out by isolated strain PP9. From the present investigation, it was clear that slag replacement along with bacterial treatment of motar cubes by PP9 effectively enhanced the durability and permeation properties. Compressive strength increased by 28% in bacterial treated specimen with 30% slag replacement (30SBT) when compared to the control motar cube. Water absorption property of 30SBT specimen decreased by 8 times when compared to the control. Scanning electron microscopy analysis further supported the involvement of bacteria in formation of calcite and vaterite polymorphs of calcium carbonate on cement motar cubes. Hence, bacterial treatment along with steel slag replacement in building materials proved to efficiently enhance its properties as well as diminish environmental related concerns.
Keywords: Microbial Concrete, Waste Utilization, Steel Slag, Biomineralization, Staphylococcus pasterui